Solar Coronal Mass Ejection and Post–Coronal Mass Ejection Blob Formation in Two-fluid Simulations - J. C. Du; Z. W. Ma (The Astrophysical Journal)
A coronal mass ejection (CME) and post-CME blob phenomena in the solar atmosphere, associated with shear flow and convergent flow perturbations in the photosphere, are investigated using a resistive two-fluid (electron–ion) code. It is found that there are notable deviations between the two-fluid and previous magnetohydrodynamic simulations. In this two-fluid approach, the decoupling motions of ions and electrons leads to the emergence of an additional electric field. With expansion of a magnetic arcade associated with the footpoint shear flows, a thin current sheet is formed and a series of magnetic reconnections occurs in the lower region of the central magnetic arcade. The initial reconnection gives rise to a rising magnetic island, displaying typical CME characteristics. Subsequent reconnections produce smaller, more rapidly ascending blobs. These smaller blobs ultimately merge with the primary CME core, thereby accelerating its ascent.